Evaluation of Arts-Based Performance Tasks in Hybrid Classes - Marlon Fernandez (JPAIR Institutional Research Journal)
Performance tasks are the major requirements that senior high school students demonstrate, especially from the core art subject, Contemporary Philippine Arts from the Regions (CPAR) in De La Salle Santiago Zobel School (DLSZ). CPAR provides annual strand-based art-integrated exhibitions and performances in various strands in DLSZ. Amidst the ongoing pandemic and the new hybrid concurrent class setup in the setting, three (3) varied art-integrated performance tasks were mounted. The aim of this small-scale ethnographic action research study is to analyze the development of the art-integrated performance tasks through document analysis in the Arts & Design Track, HUMSS, and ABM strands; identify its educational objectives by conducting a structured interview of the teachers involved (u=9); explore the perceptions of the integration from selected students (n=7); and evaluate the success ratings based on the educational objectives of the integration by conducting a survey from the students (n=149) using 5-point Likert scale. Results revealed that the art integration of the subjects is generally perceived as connected and the art-integrated performance tasks from each strand are deemed beneficial, challenging, excellent, and very successful. Further studies are needed to discuss the issues in a larger context and on the socioemotional impact of the students and teachers involved.